The Cities in East Sumatera after the Development of Plantation Industry 1863-1942 - Sumarno, Edi; Karina, Nina; Ginting, Junita Setiana; Handoko, Handoko (Budapest International Research and Critics University, 2019)
The ports in East Sumatra were located on the banks of the riverbefore the presence of plantations.These traditional cities underwent some changes after the presence of plantations, where the cities on the riverbank changed intothe cities in the middle of the plantation. The new cities that emerged after the development of plantations were formed or initiated by the plantation party and the Dutch Colonial government in East Sumatra. The purpose was for the cities to become the administrative center of the plantations and government. Why did the colonial government or plantations build new cities? And howwas the development of the old cities and the new cities?